(untitled) (Kronika Bydgoska, 2012)
In May 2010, a rise on the Vistula River resulted in a a backwater on the Brda River in Bydgoszcz, the rangę o f which turned out to be the largest for over 40 years. This backwater caused numerous floodings in the city area. The course o f hydrological phenom ena on the rivers in the area of Bydgoszcz in recent years shows that the flood risk along the lower Vistula River and its tributaries is still current. In case o f Bydgoszcz, an unfavourable circumstance is the progressive systematic development o f riverside areas. In connection w ith this, rises even significantly lower than the maximum recorded in the city’s history can cause heavy materiał losses.